Penerapan Motif Minangkabau sebagai Elemen Dekoratif pada Keramik Hias dengan Teknik Wax Resist - Haniful Furqon; Angga Elpatsa (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The development of ceramic craft in West Sumatra reveals significant potential for productive economic sectors due to the abundance of clay. This study focuses on applying Minangkabau motifs as decorative elements on ornamental ceramics using the wax resist technique. The aim is to integrate traditional Minangkabau designs into ceramics, introduce a new decorative technique, and preserve local culture through craftsmanship. The method employed includes five stages of the art consortium: preparation, elaboration, synthesis, realization of the concept, and completion. The result is seven ceramic pieces featuring motifs such as “Pucuak Rabuang” and “Carano Kanso,” utilizing stoneware clay and wax resist techniques to create unique designs while enhancing appreciation for ceramic art and local culture. The implications of this work include improved understanding of ceramics and cultural motifs, as well as encouragement for artisans to incorporate cultural elements into their products. This work is expected to contribute to the development of ceramic craft in West Sumatra and serve as a study resource for art education institutions.